EVALUASI KEBIJAKAN PEMEKARAN DAERAH KABUPATEN LAMPUNG BARAT - administratio Department; Dewi Ayu Hidayati (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This study aims to determine how the evaluation of West Lampungregency’s expansion is viewed from the public perception, the knowledge ofsociety, and the positive and negative effects of the expansion policy. This is akind of descriptive-qualitative research. The data collection was done by in-depthinterviews, observation and documentation. Then the collected data wereanalyzed through three stages, i.e. data reduction, data presentation, anddrawing conclusions/verification. The result of the research shows thatthe expansion of the West Lampung is highly approved by majority. This is becausethe expansion is not very influential for the society, since they are much lessfamiliar with the regional expansion. The positive effect is that largelygovernment agencies feel easier to carry out their duties and functions as issuesthat should be addressed in the Pesisir Barat have now been reduced. Whereas, itsnegative effects are the decline in revenue, the rise of unemployment, the lost ofculture, and even tourisms which no longer belong to the West Lampung. Theconcept of the expansion is still understood so simply and Liwa’s society still feelunfamiliar with this project. People are still waiting for what the government willdo, even some people are skeptical about this project. Keywords: evaluation of policy, expansion, West Lampung regency